Preface: Thermal Processing and Thermophysical Properties of Metals, Intermetallics, Alloys and Composites 2019 (TPTPMIAC2019) - Rotaru A.; Riposan I.; Manasijević D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
nema